Retenção e disponibilidade de água em solos com fragmentos grosseiros - Pereira, Caroline Andrade (2021)
Accurate characterization of hydraulic properties and water retention parameters in soils with coarse fragments (Ø ≥ 2 mm) is crucial to understanding the capacity of these soils to store and make water available to plants. However, coarse fragments make it difficult to sample and determination hydraulic properties and soil water retention parameters. This work was divided into three articles. The objective of the first article was to evaluate whether reducing the size of coarse fragments is a suitable strategy for accurate measurements with dew point potentiometer. Coarse fragments were successively fractured (initial size 38-4 mm for size classes 4-2, 1-0.25 and < 0.25 mm). For each size class, the retention properties (water content versus water potential) were determined with a dew point potentiometer. It was found that the size of the coarse fragments can be reduced up to 0.25 mm without affecting the retention properties. Therefore, this is a suitable strategy to allow accurate with dew point potentiometer measurements in soils with coarse fragments. The objective of the second article was to evaluate if the sampling and waterproofing techniques of soil blocks with preserved structure enable consistent determination of the water retention curve of soils with different amounts and sizes of coarse fragments. Blocks of soil with preserved structure were collected in the superficial layer of soils containing coarse fragments and waterproofed with paraffin to determine the water retention curve. Sand and saturated ground quartz were used on one of faces of the soil blocks to improve their contact with the porous media of the sand column and Richards chamber. The conformation of the water retention curves resembled the “S” shape typical of the water retention curves of many soils, indicating that the drainage caused by the successive decrease in pressure head was coherent. The use of sand and ground quartz allowed good contact of the soil blocks with the porous media of the sand column and Richards chamber, respectively. Soil blocks with preserved structure and paraffined allow consistent determination of the water retention curve of soils with coarse fragments. The objective of the third article was to characterize the retention and availability of water and their relationship with the amount of coarse fragments of different sizes and mineralogy in soil samples with preserved structure. Blocks of soil with preserved structure were collected in the superficial layer of soils containing coarse fragments and waterproofed with paraffin to enable the handling of these samples and determination of water retention in different pressure head. Coarse fragments little porous reduce total porosity and water retention in the soil. On the other hand, porous coarse fragments contribute to soil water retention. The effect of coarse fragments on soil water retention depends mainly on the porosity of the fragments. Therefore, coarse fragments must be considered when determining of the physical-water properties of soils.